Interpretasi Hasil Tes Penilaian Acuan Norma (PAN) dan Penilaian Acuan Kriteria (PAK) dalam Evaluasi Pembelajaran Bahasa Arab - Syafruddin, Lisa; Herdah, Herdah (Ta'limi | Journal of Arabic Education and Arabic Studies, 2025)
Learning outcome assessment plays a strategic role in improving the quality of Arabic language learning. Learning evaluation plays an important role in measuring the achievement of student competencies. One of the commonly used approaches is the interpretation of test results based on Norm Reference Assessment (PAN) and Benchmark/Criteria Reference Assessment (PAK). This study aims to review the effectiveness of these assessment approaches in the context of Arabic language learning. The method used is library research, by reviewing primary and secondary literature such as scientific journals, books, and academic documents. The selection of sources is based on the suitability of the theme, recency, and credibility. The analysis techniques applied are content analysis and thematic synthesis to explore patterns of test score interpretation in learning evaluation. This study also highlights how educators can link test results with criterion or norm-based assessments proportionally and contextually. The results of the study indicate that the criterion-based approach tends to be more applicable in supporting students' mastery of maharah lughawiyah and supporting directed learning. Meanwhile, the norm-based approach remains relevant in the context of large-scale selection or evaluation. Thus, the selection of the right assessment method, accompanied by an understanding of the evaluation function, will encourage the achievement of learning objectives more effectively and comprehensively.